Information on Advanced Study Assisted by Adobe Flash Media to Increase Motivation for Advanced Studies - Juminah, Juminah; Sugiyo, Sugiyo; Awalya, Awalya (Jurnal Bimbingan Konseling, 2019)
The purpose of this study is to determine the effectiveness of information services in advanced studies assisted by Adobe Flash media in increasing motivation for further studies in high school students. The experimental research method uses the design of one group pre-test – post-test involving 8 students who have very low motivation for further study. The results of this study indicate that the motivation of further study of students before being given information on further study assisted by Adobe Flash media, the average motivation for further study was 94.25 (SD = 6.29), then an increase after being given information services with Adobe Flash assisted study of 294.25 (SD = 9.57). The paired sample t-test results showed that Adobe Flash assisted information services were effective in increasing the motivation of further study of high school students (t(7) = 51.396, p < 0.01). This study confirms that information services for further studies assisted by Adobe Flash media can be applied to increase the motivation for further studies of high school students.